Alcatraz revisited - Morrison, Keith (Macau Business, 2022)

The business of social justice in Macau - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | As Macau rebuilds its post-pandemic economy, one could be forgiven for believing that the good life for all has arrived, as evidenced in the manifest opulence on display in its up-market shopping malls. However, this is not the case; social justice needs attention in Macau.
Section: Macau Business

Linguistic and economic capital in Macau - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Macau wisely looks to mainland China, South-East Asia, and Portuguese-speaking countries, as part of its economic diversification. However, to be a player on the international stage and world-wide market, it must look wider, and, hence, the standard of English in Macau must improve dramatically and urgently.
Section: MAG

Chatting about chatting - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Many employers in Macau expect their employees to have received higher education (HE). This returns to the endless question of what HE is for; is it for job knowledge and skills acquisition, attitude development, thinking abilities, creativity, problem solving, how to learn, or what? What and whose knowledge?
Section: Macau Business

Sunshine and shadows - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | The recent euphoria over Macau’s economic resurrection should not mask the long-standing challenges facing its society and values. Sunshine creates shadows in which can lurk a range of pathologies.
Section: Macau Business

Games of chance - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Here we are, back in full-throttle summer tourism in tiny Macau, with visitors galore, lines of tourist coaches everywhere, and the casinos back on course to welcome gamblers. However, gambling reaches much wider than Macau’s casinos.
Section: Macau Business

Conditional internationalism in Macau - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Just when diversification is the name of the game in Macau, and with the manifold benefits of diversity that internationals can bring, how sensible is it to treat its international non-resident workers so poorly, and with lamentable transparency and accountability?
Section: MAG

Dreaming of diversification - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Once upon a time there was a cockerel who succumbed to flattery when a wily fox told him that he had the most magnificent singing voice, especially when he sang with his eyes closed tightly.
Section: MAG

Santa Claus is not coming to everyone in Macau - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Macau Business | December 2023 Keith Morrison – Author and educationist
Section: Macau Business

Tipping points and economic recovery in Macau - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | New year; old problem. As the pandemic rolls on, so many calls for economic diversification in Macau as a survival strategy have been heard, loud and long, that, as the law of diminishing returns tells us, their effects recede.

Getting out of a problem - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Macau should be proud of its protective handling of the Covid-19 pandemic, as it has managed to contain its spread, and many of its citizens have been able to lead a more normal life than in other parts of the world. We should be grateful for this.

Escape from Macau - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Macau used to be very appealing to expatriates from across the world. Its low tax rate (and zero tax for low-paid expatriates), blends of cultures, business opportunities, life style, history, unique features and a host of other attractions fuelled an ongoing supply of foreign nationals to this small, unusual city. It is an interestingly idiosyncratic place in which to live. For many expatriates, Macau has been home, in many cases reaching back more than one generation. This is perhaps unsurprising, as people here are typically exquisitely polite, a delight to be with, and very accepting. Its acceptance of differences in values is an example to countries across the world. Macau is a safe place to live.
Section: Macau

Mind your own business - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Across the world, a civil service job pays well and is secure. Not bad if you can get it, with competitive entry to it by hordes of applicants.
Section: Macau Business

The wonderland of Macau's talent development - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | The world is full of interesting paradoxes that befuddle the mind. Or, as the delightful chapter in Alice in Wonderland put it: ‘‘curiouser and curiouser!’’.
Section: Macau Business

What's behind Macau's business disaster? - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Business 101. When companies plan their business models, typically they must consider, amongst other matters: their products and/or services; demand; market(s) and their environments (economic, political, cultural, social); existing, potential, and likely competition; start-up and ongoing costs and expenses; emergency funding; marketing and promotion; income streams, revenue, and delayed profit; sales; distribution; cash flow; profit margins, gross and net; liabilities; risk analysis, evaluation, and handling; constraints and the ‘what if’ factor; flexibility, adaptability, and adjustment.
Section: Macau Business

And the award goes to... - Morrison, Keith (Macau Business, 2022)
Macau, MNA, Opinion | The Macau government recently approved its first reading of a new bill to attract Macau locals to return to Macau to work. Simultaneously, Macau’s Secretary for Social Affairs and Culture was reported as saying that if Macau could create a better environment and conditions, then ‘local talents who are abroad will surely be interested in returning to Macau’.
Section: MNA

Getting the agenda right for higher education in Macau - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Here we are, at the start of a new academic year in Macau’s higher education (HE). What will students learn? What kind of people are the institutions turning out? For example, look at the thousands of students studying business and technology in Macau, the big recruiters in HE.
Section: Macau Business

A dose of lateral thinking - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | The late psychologist, business and management consultant Edward de Bono gained a worldwide reputation for ‘lateral thinking’, which included his ‘six thinking hats’ and ‘tools for thinking’. Though his work is arguably only plausible pseudoscience, his ‘tools for thinking’ remain interesting. Consider some of these from his Cognitive Research Trust (CoRT), in approaching planning, e.g.: CAF (Consider All Factors); EBS (Examine Both Sides); and OPV (consider Other People’s Views). Here I apply them to Macau.
Section: Macau Business

Sustainable development or survival of Macau? - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | In June of this year, a publication entitled ‘Macau’s sustainability and diversification’ noted that Macau’s ‘economic volatility caused by an unbalanced industrial structure restricts the diversified development of society. Economic diversification is the only way for Macau to achieve sustainable development’. Nothing new there, and, anyway, such a singular view is unconvincing. What about other aspects of society? Diversity is not singular, and it requires inclusion.
Section: Macau Business

A Christmas present worth having - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | When the casino resorts applied for the first licenses to operate in Macau, one of the commitments that they made was to serve the Macau society. Many of them have honoured those commitments outstandingly well, and continue to do so, and in ways too many and diverse to list here.
Section: Macau Business

A risky new year - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Despite the welcome optimism expressed at the government’s plans to resurrect Macau’s economy, its economic recovery will continue to suffer from having had the rug pulled from under its feet by the zero-Covid policy, however well intentioned.
Section: Macau Business

Human capital investment outflanked by Macau's needs - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | As Macau strives to revive its post-pandemic economy and to reinject life into its ailing society, calls for investment in human capital resurface, alongside endless mantras of economic diversification which, for years, seem to have fallen on deaf ears, and together with plans for further infrastructure development and construction which have already turned Macau into a concrete jungle.
Section: Macau Business

The international recruitment obstacle race in Macau - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Macau’s development of international and tertiary sector industries is the watchword for its long-overdue diversification. Is Macau ready for this?
Section: Macau Business

Prize-giving time for Macau - Morrison, Keith (Macau Business, 2020)

The Genesis of a New Year | Macau Business - Morrison, Keith (Macau Business, 2021)

Higher Education in Macau: waxing or waning? - Morrison, Keith (Macau Business, 2021)

Who’s kidding whom in Macau’s English performance? - Morrison, Keith (Macau Business, 2021)

Three cheers for critical thinking | Macau Business - Morrison, Keith (Macau Business, 2021)

Copycat Macau? - Morrison, Keith (Macau Business, 2021)

Travel Sickness - Morrison, Keith (Macau Business, 2021)

How suitable are you for Macau’s workforce? - Morrison, Keith (Macau Business, 2021)

Macau’s gaming culture hits higher education - Morrison, Keith (Macau Business, 2021)

The scourge of construction - Morrison, Keith (Macau Business, 2022)

Twilight of the idols - Morrison, Keith (Macau Business, 2021)